Design and Build a Human Resource Information System Application at PT XYZ - Rahmatika Rahmatika; Ardhi Dinullah Baihaqie; Nasrulloh Isnain (Journal of Information System, Informatics and Computing, 2022)
HRIS is a system that helps manage problems related to the management of human resources in the company. It contains data about employees, their qualifications, and their performance. Managing human resource data at PT. XYZ can be a challenge in itself. There are a variety of different systems and databases to manage, and it can be difficult to keep track of all the information. Companies find it difficult to obtain information about human resources because they are still managed manually. To help with these problems, a Human Resources Information System was created that can assist the personnel department in carrying out their duties, starting from the recruitment process to preparing reports, and producing information that can be used for decision making. The Model View Controller (MVC) design pattern is a popular way to structure code for software applications. This pattern is used in computer software development, where this pattern divides the application into three main layers: Model, View, and Controller. The model is the representation of the data model in the database, the View is the view between the user and the Controller is the application business logic processor. This makes the application easier to develop at a later date. There are various days that are most suitable for the company, depending on its development and needs.